iSantri for Kyai Galang Sewu Islamic Boarding School - Dyah Arumsari; Lydia Christiani (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2021)
This study discusses the perception of the iSantri application by the santri from the Kyai Galang Sewu Islamic Boarding School. The research method used in this research is descriptive qualitative with a case study approach. Informants were obtained through purposive sampling with seven informants using the iSantri application at the Kyai Galang Sewu Islamic Boarding School. Data collection techniques used were observation, interviews, and document study. The results of this study indicate that the perception of the iSantri application is well received by the santri to increase their knowledge of Islam, make it easier to interpret Islamic religious books, get additional references for interpretation and complete the meaning of Islamic religious books, and also as an alternative source of learning at the Kyai Galang Sewu Islamic Boarding School. The stages of accepting the iSantri application are based on the use of the iSantri application by the santri of the Kyai Galang Sewu Islamic Boarding School who use the iSantri application as a medium to support the learning process. The iSantri application provides easy access without having to wait so long to get information on Islamic religious books. The usefulness and ease of access to the iSantri application encourage the emergence of the intention and attitude of the santri to continue using the iSantri application.